The Influence of Parental Status on Depression and Self-Esteem Among Adolescents in Ghana: A Case Study of The Christian Methodist Senior High School - Ellen, S. (University of Ghana, Legon, 2013)
Divorce, single parenting and issues associated with parental status on an adolescent’s wellbeing specifically, adolescents’ depression and self-esteem has been on an increase worldwide and Ghana is no exception. This study was aimed at examining the influence of parental status on depression and self-esteem of adolescents in Ghana after noticing that adolescents going through formal education face many challenging situations as a result of diverse marital issues of their parents. Specifically, the study was aimed at examining if a significant difference existed between parental status on depression and self-esteem of Ghanaian adolescents. It also investigated relationship between depression and self-esteem among adolescents. It further examined if a difference existed between female adolescents who live with their single-parent mothers and male adolescents who live with both parents on depression. Lastly, it examined whether a significant sex differences existed among adolescents on self-esteem. In all, 308 respondents were selected across the three stages of the senior high educational level to respond to the questionnaire. Findings of the analyses revealed that adolescents of single-parents had significantly more depression than adolescents of intact-parents. Adolescents of intact-parents had significantly higher personal self-esteem and general self-esteem than of single-parents but there was no significant difference existed between them on social self-esteem. There was a significant negative relationship between depression and social self-esteem, personal self-esteem, and general self-esteem. However, there was no significant interaction effect observed between sex (male and female) and parental status (single-parent-father, single-parent-mother, and intact parents). Male adolescents had significantly higher social self-esteem, personal self-esteem, and general self-esteem than female adolescents. Necessary implications and recommendations to the educational sector, clinicians and other relevant mental health professionals have been made.
Thesis (MPhil) - University Of Ghana, 2013